(3GdYUQ Gdfhhj hGdbhI GdfhhjI aj GdYGde GdeYGUQ (B:s (3GdYGde jacQ hjJCed (B/s - (3YHO GdaJGM, ESeGYjd,s 1954- ((3GdbGgQI (B:s (3GdecJH GdYQHj ddeYGQa,s, 2018)
(3jJfGhd cJGH (B((3GdYUQ Gdfhhj hGdbhI GdfhhjI aj GdYGde GdeYGUQ (B: (3GdYGde jacQ hjJCed(B) (3hGdPj bGe HJCdjag (B%22(3ESeGYjd YHO GdaJGM YHO GdcGaj(B%22 (3aj MhGdj (B(443) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdWGbI GdfhhjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdJLSS Ydi UfGYGJ GdbfHdI GdfhhjI, gd MXQ GdGfJTGQ Gdfhhj LGOG haGYdG, eQI KGfjI efY GdGfJTGQ Gdfhhj, gd GdbhI GdfhhjI ddQOY abW, gd gfGc ef jSJWjY fhhjG JMhjd eSGQ GdJGQjN GdEfSGfj, JMOjGJ GdbhI GdfhhjI, CSQGQ Gdehba Gdfhhj GdESQGFjdj, GdbfHdI GdfhhjI GdESQGFjdjI ef GdHOGjI MJi, GdShajJ jQGbHhf GdeZGeQI GdfhhjI GdESQGFjdjI, eUQ hGdYUQ Gdfhhj GdPj de jHOC MJi GdBf, EjQGf hGdbhI GdfhhjI(B.s
(3JUeje GdZdGa (B: (3eMeO YeGQ(B.s
Keywords: (3GdWGbI GdPQjIs; (3GdWGbI GdfhhjIs -- (3ebGdGJ heMGVQGJs; (3GdCSdMI GdfhhjIs